Bioinks for biofabrication: current state and future perspectives. Issue 1 (January 2017) - Prendergast, Margaret E; Solorzano, Ricardo D; Cabrera, Danny
Recent progress in 3D printing technologies is leading a revolution in cell culture methods. These systems rely heavily on bioinks, the raw cells and biomaterials used to create these 3D cultures. These formulations, ranging from cell suspensions to hard acellular thermoplastics, must function with 3D systems and offer biocompatible environments that mimic in vivo tissue characteristics. Although much progress has been made for the production of increasingly complex reproducible 3D tissues, a full biofabrication platform with both improved technology and superior bioinks must be developed. Here, important properties for these materials are examined; recent advances in bioinks are summarized; and finally, future considerations for 3D biofabrication are discussed.